Perceived Consumption Values, Satisfaction and Loyalty in the Tourism: Case of Malaysia - Shu Wan Tan, Adeline; Falahat, Mohammad; Kai Sia, Bik (International Journal of Engineering and Technology, 2018)
Domestic tourism is a substitute for outbound travel has a potential to create income and employment in the home economy. These potentials also create opportunities through the linkage at destinations. This study extent the concept and evaluates the empirical evidence of the relationship between perceived consumption values toward tourism loyalty. Drawn from revised framework of the Sheth-Newman Gross Model of Consumption Values and the European Consumer Satisfaction Index (ECSI), we examine the relationship of perceived consumption values, tourist satisfaction and tourist loyalty. Data obtained from 255 tourists visited the state of Malacca, Malaysia. The results indicated that tourist loyalty is affected by perceived consumption values and fully mediated by tourist satisfaction. The findings provide valuable insights to the policy makers, industries and academics in developing strategies and exploring possible factors to consider in tourism sector and thus, boost the national economy. As for policy makers, this study can be seen as exploitation to increase the influx of international tourists by implementing policies or improving tourist spots. Â Â